India's Open Door to Foreign Universities: Less than Meets the Eye - Altbach, Philip (International Higher Education, 2010)
India may finally open its doors to foreign higher education institutions and investment. India's higher education faces severe problems of capacity and quality. This lack of capacity will affect India's new open-door policy. It will be unable to adequately regulate and evaluate foreign institutions. Though the system needs systemic reform, it is impossible for foreigners to solve or even to make a visible dent in India's higher education system.